SUATU TINJAUAN HUKUM TERHADAP RETUR PENJUALAN DALAM ASPEK-ASPEK HUKUM PERJANJIAN JUAL BELI - Fery Bernando Sebayang; I Nyoman Wita (Kertha Negara : Journal Ilmu Hukum, 2013)
Sales Returns is the return of the goods from the buyer for certain things, maybe because damaged in transit, defective or not in accordance with the specifications of the buyer. Purchase agreement is a contract is a contract in which one party to a called party sellers attach itself to hand an object which is the object of the agreement. While the buyer commit himself to pay the price of the object that the agreement has been agreed by the parties. This article will explain what the legal effect on the return of the goods from the buyer to the seller. This paper also describes the legal efforts in progress that can be used if the aggrieved party in the purchase agreement.